Climate Services Ecosystems in times of COVID-19 - Goddard, Lisa; González Romero, Carmen; Muñoz, Angel G; Acharya, Nachiketa; Ahmed, Shamsuddin; Baethgen, Walter; Blumenthal, Benno; Braun, Mélody; Campos, Diego; Chourio, Xandre; Cousin, Rémi; Cortés, Catalina; et al. (2020)
Faced with the greatest public health crisis of our time, people must work together and learn from each other to overcome the complex challenges facing our communities, countries, and the world. Climate-related hazards are one of those challenges; they exacerbate already challenging public health conditions and impact not just people, but also the infrastructure, trade, and community support on which society depends. Through “Adapting Agriculture to Climate Today, for Tomorrow” (ACToday), the first of Columbia University’s Columbia World Projects, proactive interactions in six developing countries help identify and create the local climate service ecosystems needed to address food security, agricultural sustainability, and nutrition goals. In times of crisis and uncertainty, such as the current global pandemic of COVID-19, the preparation for climate impacts often turns toward reaction and response. However, climate risks remain unabated despite the COVID crisis; systems that make it easier for already-stressed decision-makers to understand and manage climate risks – and opportunities – are critical. Together, society must prepare for and manage the challenges that it can anticipate in order to be more resilient to those it cannot, and climate services ecosystems can help in this regard.